185: Subjective Fever Assessment in Children by Palpation – Are Fathers as Reliable as Mothers?. Issue 6 (1st June 2014) - Jacobson, D; Steele, M; Kozer, E; Balis, C; Cheng, J; Rosenbloom, E
Abstract: BACKGROUND: Fever as a chief complaint is one of the common presenting problems for the pediatric patient in the emergency department. Although previous studies have demonstrated reliability in mothers' tactile fever assessment, there are no studies that have investigated the reliability of such measurement in fathers. OBJECTIVES: The objective of this study was to assess the reliability of fathers compared to mothers at detecting fever by palpation in their children. DESIGN/METHODS: With Hospital Ethics Board approval, the inclusion criteria consisted of children zero to four years of age with both parents, and in stable condition, presenting to the emergency department with a complaint which included fever. After consent, parents were separated and blinded to one another. In addition to being asked for their demographic information and their usual methods of fever determination, each parent was also asked if their child currently had a fever, and if so, asked for an estimate of the temperature. Emergency department nurses then obtained a rectal temperature with consent. RESULTS: A total of 435 parents submitted complete forms. Sensitivity and specificity of mothers in identifying 'any fever' in their child by palpation were 84.5% and 44.9% respectively, and for fathers, 89.1% and 35.4%. For fevers greater than 39°C in triage, mothers' sensitivity and specificity in assigning a fever greater than 39°C by palpation were 48.4% and 76.5% respectively, and for fathers, 47.4% and 65.4%. In this latter category, fathers' specificity of assessment of fever greater than 39°C was significantly lower (P<0.05). As well, in both 'any fever' and fever greater than 39°C categories, unemployed participants were significantly inferior in their assessment compared to those working 20 to 60 h/week; odds ratio of 0.50 and 0.53 respectively. CONCLUSIONS: Fathers' specificity assessment of 'high' fevers was poorer compared to mothers' assessment. Furthermore, in groups of unemployed persons, regardless of degree of fever, this group performed inferiorly. Treating the description of tactile fevers as any diagnostic test, sensitivities greater than 80% by fathers and mothers indicates palpation to be a fairly good screening test. Therefore, dismissing a parent's report of fever by palpation is misguided.